Pengaruh Beban Kerja dan Kompensasi Terhadap Kinerja Karyawan Rindang Coffee Shop di Palembang - Ramadani, Lulu Alfia; Halin, Hamid; Purnamasari, Endah Dewi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the influence of workload and compensation on the performance of Rindang Coffee Shop employees in Palembang. The data used is primary data and secondary data. Data collection techniques include questionnaires, observations and interviews. The technique used for sampling was nonprobability sampling with a saturated sampling technique or quantitative method, so that the researcher took the entirepopulation, namely 30 employees. The instrument used in this research was Google Form. This research uses a questionnaire method (Questionnaire) with the aim of collecting data by filling out the questionnaire provided "The Influence of Workload and Compensation on the Performance of Rindang Coffee Shop Employees in Palembang." Based on the results of the research and analysis that has been carried out, X1 has a significant influence on theperformance of employees at Rindang Coffe Shop Palembang (Workload) and X2 (Compensation) have a significant influence together on Y (Employee Performance) at Rindang Coffe Shop Palembang. Thus, the research results can be concluded that the research hypothesis "The Influence of Workload and Compensation on the Performance of Rindang Coffee Shop Employees in Palembang can be tested for truth or can be accepted."